Primordial germ cells profile incubated for 24 hours in phosphate buffer saline [-] solution - Tatan Kostaman; Soni Sopiyana (Indonesian Center for Animal Research and Development (ICARD), 2017)
Gonadal development is a sequential process that can be divided into three major events: the PGCs migration, sex determination and gonadal differentiation. This study was aimed to see the development of PGCs isolated from the gonads of embryos after being incubated for 7 days and then was incubated using a solution of Phosphate Buffer Saline (PBS) [-]. The developing gonad can be isolated from 7 days old chick and can be incubated at a temperature of 37.8oC in a solution of PBS [-]: without Ca2+ and Mg2+. The release of gonadal PGC was observed within 1, 8, 16, and 24 hours after the embryonic gonad was placed in a PBS solution [-]. The results showed that PGCs can be separated from gonadal tissues and can be collected by entering the developing gonad to the PBS [-] solution. The highest percentage of PGCs and survival rate was obtained after gonad was incubated for 1 hour and was not different with 8 hours (P>0.05). Those result was significantly different (P<0.05) with the 16 and 24 hours incubation. The highest purity rate percentage was in the 8 hours incubation, but did not show a significant difference (P>0.05) with the 1 and 16 hours incubation. The percentage of the purity differed (P<0.05) after the 24 hours incubation. It can be concluded that the most appropriate incubation time to obtain PGCs from the KUB chicken embryonic gonad is no more than 8 hours.